2022
DOI: 10.1093/rheumatology/keac581
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of plasma inflammatory proteins reveal biomarkers predictive of subsequent development of giant cell arteritis: a prospective study

Abstract: Objective To investigate the relation between biomarkers of inflammation and subsequent development of giant cell arteritis (GCA). Method Participants in the population-based Malmö Diet Cancer Study (MDCS; N = 30447), established 1991–1996, who were subsequently diagnosed with GCA, were identified in a structured process. GCA-free controls, matched for sex, year of birth, and year of screening were selected from the study coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Innate check-point dysregulation contributing to GCA development may be influenced by metabolic factors ( 89 ). The importance of T-cell dysregulation has been further underlined by the recent demonstration of elevated T-cell related cytokines years before disease onset ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Innate check-point dysregulation contributing to GCA development may be influenced by metabolic factors ( 89 ). The importance of T-cell dysregulation has been further underlined by the recent demonstration of elevated T-cell related cytokines years before disease onset ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that plasma levels of IFN-γ and other proteins related to T cell function may be elevated years before clinical disease onset ( 78 ), further underlining the importance of this pathway and suggesting that it may drive very early disease mechanisms.…”
Section: Cytokine Signatures In Gcamentioning
confidence: 99%
See 1 more Smart Citation
“…Very interesting data are provided by a Swedish study on the biomarkers that were measured in people prior to the development of GCA (22). In this study, the authors used a large cohort of 30,447 patients-initially developed to study cancer-and identified 94 cases of incident GCA.…”
Section: Monocyte Chemoattractant Proteinmentioning
confidence: 99%
“…Novel biomarkers from translational may increase the probability to identify GCA among patients with new onset PMR. Among them angiopoietin-2/1 ratios and metalloproteinase-3 levels (22) as well as interferon-γ levels and T-cell activation (23) were identified and proposed. Another clinical challenge in GCA is represented by the possibility of distinguishing active from inactive disease.…”
Section: New Insights Into Gca Imaging Biomarkers and Clinical Unmet ...mentioning
confidence: 99%